Long non-coding RNAs defining major subtypes of B cell precursor acute lymphoblastic leukemia - James, Alva Rani; Göllner, Stefanie; Müller-Tidow, Carsten (Journal of hematology & oncology, 2019)
Long non-coding RNAs (lncRNAs) have emerged as a novel class of RNA due to its diverse mechanism in cancer development and progression. However, the role and expression pattern of lncRNAs in molecular subtypes of B cell acute lymphoblastic leukemia (BCP-ALL) have not yet been investigated. Here, we assess to what extent lncRNA expression and DNA methylation is driving the progression of relapsed BCP-ALL subtypes and we determine if the expression and DNA methylation profile of lncRNAs correlates with established BCP-ALL subtypes.
Gesehen am 29.03.2019